2020
DOI: 10.1183/23120541.00036-2020
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among patients with COPD according to smoking status: a Danish nationwide case�control study of 21 184 patients

Abstract: IntroductionDepressive symptoms appear more often among patients with chronic obstructive pulmonary disease (COPD) and are associated with reduced disease control and increased mortality. Both smoking and COPD increase the risk of depressive symptoms. Whether smoking cessation among COPD patients affects the occurrence of depressive symptoms is unknown. We hypothesised that smoking cessation in patients with COPD leads to reduced use of antidepressants and fewer admissions to psychiatric hospitals with depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…It has also been reported that men with COPD take part in significantly more physical activity than women and that physical activity relieves their symptoms, improves their quality of life and decreases the risk of exacerbations [ 13 ]. Additionally, in the current study, being a smoker was related to an increased likelihood of CMDs in women, which supports previous reports [ 60 , 71 ]. Female COPD patients are more likely to suffer from depression and anxiety than their male counterparts, with manifestations that can be severe [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has also been reported that men with COPD take part in significantly more physical activity than women and that physical activity relieves their symptoms, improves their quality of life and decreases the risk of exacerbations [ 13 ]. Additionally, in the current study, being a smoker was related to an increased likelihood of CMDs in women, which supports previous reports [ 60 , 71 ]. Female COPD patients are more likely to suffer from depression and anxiety than their male counterparts, with manifestations that can be severe [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…BD (and probably psychiatric disorders in general) remains a risk factor for persistent smoking compared with unaffected individuals. 56 Tobacco smoking has been associated with a wide range of psychiatric/psychological and non-psychiatric difficulties in BD 25,38,44 and it decreases the plasma levels and the effectiveness of several psychotropic drugs. 5 Finally, smoking also impacts quality of life of patients with BD.…”
Section: Discussionmentioning
confidence: 99%